The Rio Quantum Network: a reconfigurable hybrid multi-user metropolitan quantum key distribution network - Temporão, Guilherme P.; Melo, Fernando R. V. Bandeira de; Khoury, Antonio Z. (Anais do Workshop de Redes Quânticas (WQuNets), 2024)
This paper describes the current status of the Rio Quantum Network project, a metropolitan quantum communication network under construction connecting four research institutions in the state of Rio de Janeiro through optical fibers from Rede Rio de Computadores / FAPERJ and a 7-km free space link. The Twin-Field Measurement Device Independent Quantum Key Distribution (TF-MDI-QKD) protocol is being implemented to enable secure communication between any two network nodes independently, without the need for trusted nodes. The main challenges of the practical implementation of the network will be presented and discussed.